Enhancing Educational Outcomes by Boosting Artificial Intelligence Application in Personalized Learning - Gu, Peiyu (Science Insights Education Frontiers, 2024)
As the social expectation of the standards of talent training increases, the society has become more aware of the limitations of the traditional one-size-fits-all education paradigm and has endeavored to develop educational paths that can better cater for individually different needs of the learner. Personalized learning, as an important instructional strategy in the new era, is intended to make education more pertinent to the unique needs, learning style, and ability of each individual student for the purpose of optimizing their educational outcomes (Kaswan et al., 2024). The rise of artificial intelligence (AI) makes changes to conventional education patterns and improvements in personalized learning possible as this technology can be harnessed to provide tailored learning materials to students, improve their information acquisition and retention, and thereby enhance their learning efficiency and educational experience (Chen et al., 2020).